Development of an Integrated Proactive Health Promotion Model for Reducing Adverse Infant Outcomes Associated with Maternal Methamphetamine Use during Pregnancy at Chiangkhan Hospital, Loei Province - Hongsa, Anchalee (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
Methamphetamine use among pregnant women in Chiangkhan District, Loei Province a Thai-Lao border area was 3.78%, exceeding the national average, resulting in high rates of preterm birth (42.59%), low birth weight (51.85%), and neonatal abstinence syndrome (NAS; 35.19%). This study aimed to develop and evaluate an integrated proactive health promotion model for reducing adverse infant outcomes. A quasi-experimental study with retrospective historical control, based on the research and development framework of Borg and Gall integrated with the PDSA cycle, was conducted over 24 months (July 2023–July 2025) in four phases: situation analysis using mixed methods (n=37), model development validated by five experts (IOC=0.89), quasi-experimental implementation comparing retrospective historical controls (n=54) and prospective intervention group (n=35), and model evaluation. Data were analyzed using SPSS version 26.0. The CHIANGKHAN MODEL (5 components: C-H-I-A-N) significantly improved outcomes. Quality ANC increased from 48.15% to 77.14% (OR=3.63, p=0.005); continuous substance use decreased from 44.44% to 14.29% (OR=0.21, p=0.002). Preterm birth declined from 42.59% to 20.00% (Adjusted OR=0.29, p=0.017; NNT=4.4); birth weight increased by 329 grams (d=0.68); and Finnegan scores decreased from 8.47 to 5.83 (d=0.97). Hospital stay was reduced by 3.1 days and treatment costs decreased by 17,340 baht per case. Multiple testing correction using the Benjamini-Hochberg false discovery rate method confirmed significance in 11 of 12 outcomes (91.7%), demonstrating robust findings. Appropriateness (x̄=4.23), feasibility (x̄=4.18), and satisfaction (x̄=4.35) were rated at high or highest levels. The CHIANGKHAN MODEL demonstrated statistically and clinically significant effectiveness with moderate-to-large effect sizes (d=0.52–1.21), robust to multiple testing corrections, and suitable as a clinical practice guideline for community hospitals in border areas.